Destruction, Death, and Drama: Narratives of Religiocide in the Hebrew Bible - Feldt, Laura (Numen, 2021)
Abstract This article analyzes active strategies for dismantling religion and discusses their role in religion demise. The aim is to throw light on how the dramatic and violent narratives of religion demolition stemming from different religious groups factor into processes and understandings of demise. I focus on religious change in the Hebrew Bible, analyzing aspects of two narratives that thematize an active dismantling of religious practices: (1) the story of the competition on Mount Carmel between the prophet Elijah and the Baʿal prophets in 1 Kings 18, involving the prophet’s mockery, denigration, and eventual killing of his religious opponents; and (2) the “reform” of King Josiah in 2 Kings 23 that involves the king instigating several different forms of destruction of religious objects and cult sites and the killing of priests deemed illegitimate. Analyzing how the dismantling activities are portrayed, I suggest that the dramatic narratives about dismantling religion form part of cultural memory in the Persian era, not in the eras they purport to depict. I discuss which roles dismantling strategies play in the narrative, and how they played a role in the identity building processes leading from ancient “Israelite” and “Judean” lived religion toward early forms of “Judaism” in the Persian era as performative group-internal communication supporting enclave characteristics. My key suggestion is that narratives about religion demolition should be taken into account in discussions of religious demise more broadly. Narratives of religion demolition are often spectacular, dramatic, and violent, and they can play important roles in forms of religious identity formation and cultural memory, especially by making apostasy appear risky within the in-group. Thus, they influence both processes of demise and understandings of religious demise in transformation processes.